Domesticating the Foreign: Opium Paraphernalia in the Skušek Collection - Motoh, Helena (Poligrafi, 2022)
The extremely large collection of objects brought from Beijing to Ljubljana in 1920 by naval officer Ivan Skušek Jr. and his Japanese wife Tsuneko Kondo Kawase, also includes several opium pipes, a few opium lamps and some other objects related to opium use. The objects are exquisitely decorated with complex motifs. While this is the main topic, the paper also aims to add context to this specific aesthetic and explore the cultural framework in which the import of these objects to Europe took place. The first part focuses on the history of opium use in China. The second part analyses the elements of the aesthetics of Chinese opium-related paraphernalia. The third, central part of the text focuses on a thorough analysis of the opium objects in the Skušek Collection and the motifs and symbols they incorporate. Finally, it presents opium paraphernalia decorated with traditional Chinese motifs and symbols as an interesting embodiment of the complex and fluid relation to the foreign, forbidden, and fascinating, and a good example of the iconographic domestication of this foreignness.